Endoscopic pilonidal sinus treatment (EPSiT) for sacrococcygeal pilonidal sinus disease: a prospective long-term study - Muhammad Amir; Farooqui, Fareeha; Latif, Sehrish; Sohaib Khan; Sibgha Aiman; Uneeb, Muhammad (Journal of the Pakistan Medical Association, 2024)
Objective: To assess short-term and long-term outcomes of endoscopic pilonidal sinus treatment for pilonidal sinus disease. Method: The prospective study was conducted at Shifa International Hospital, Islamabad, Pakistan, from July 2015 to July 2021, and comprised all pilonidal sinus cases undergoing minimal invasive endoscopic pilonidal sinus treatment who were treated by a single surgical team. The primary outcomes were duration of healing, post-operative morbidities, persistence of discharge and recurrence at 1-7 years. The secondary outcomes were operative time, return to work, cosmetic results and patient satisfaction. The patients were observed for wound healing and discharge on follow-up in the out-patient department at 1, 3, 6 and 24 weeks. They were further followed up every year through telephonic survey for persistence or recurrence of symptoms. Patient satisfaction was assessed using the 36-item Short Form Survey questionnaire filled at admission and then at 6 weeks post-surgery. Data was analysed using SPSS 23. Results: Of the 67 patients, 55(82%) were males and 12(18%) were females. The overall mean age was 25.69±8.305 years. There were 13(19.4%) patients with a history of recurrent disease and previous procedures for pilonidal sinus, while 54(80.6%) had no previous surgery. The median operative time was 35 minutes (interquartile range: 20-45 minutes). Complete wound healing was achieved in 60(89.6%) patients, while recurrence was seen in 7(10.4%). The median time off work was 2.5 days (interquartile range: 1-3 days). Patient satisfaction with the procedure was significantly high (p<0.05). Conclusion: Endoscopic pilonidal sinus treatment appeared to be a good minimally invasive surgical technique for the treatment of pilonidal sinus disease in terms of both short-term and long-term outcomes. Key Words: Pilonidal sinus disease, Minimally invasive surgery, Endoscopic pilonidal sinus treatment, EPSiT, Recurrent pilonidal sinus.